Pengaruh work-life balance terhadap kinerja karyawan melalui komitmen organisasi - Shinta Windika Putri; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Employee performance is an important thing that the company must consider because the employee's performance is expected to improve the company's quality as a whole. Several factors that can affect employee performance are work-life balance and organizational commitment. This study aims to analyze the effect of work-life balance on employee performance through organizational commitment. This research is a type of quantitative research. The sampling technique used is the total sample technique, with the total number of employees of Bank X as many as 46 people. Data was collected using a questionnaire measured by a Likert scale. The statistical analysis of this research is PLS (Partial Least Square) with SmartPLS 3.0 software. The results of this study indicate that work-life balance has a positive and significant effect on employee performance. Work-life balance has a positive and significant impact on organizational commitment. Organizational commitment has a positive and significant impact on employee performance. Organizational commitment has successfully mediated the relationship between work-life balance and employee performance. The implications based on the research results show that companies must pay attention to time management for employees to create a good work-life balance. In addition, organizational commitment must also be considered because it can impact employee performance.